Upaya Meningkatkan Kreativitas Siswa Melalui Penerapan Pendekatan Resource Based Learning Materi Lingkaran Di Kelas VIIII SMP Negeri 8 Padangsidimpuan - Saima, Yusda Herawati (IAIN PADANGSIDIMPUAN, 2017)
The learning process of mathematics in class VIII1 shows that there are still many students who are less active, creative and not independent. One of the causes of students' lack of creativity in mathematics learning is classical and conventional learning systems, namely guruselain learning that is the habit of students in mathematics learning often mimic the duties of friends, there is no desire to look for material from other sources and lack of opinion. To overcome these problems, the problem formulation in this study is whether the Resource Based Learning approach can improve student creativity on the subject of circles in class VIII1 of Padangsidimpuan Middle School 8, this study aims to improve student creativity through the application of the Resource Based Learning approach on the subject ligkaran in class VIIII of SMP Negeri 8 Padangsidimpuan.This research was conducted in class VIIII of SMP Negeri 8 Padangsidimpuan, having its address at Jl, Tengku Rizal Nurdin, Km.8 Pijorkoling Padangsidimpuan Tenggara. This research was conducted in the even semester of the 2013-2014 academic year consisting of 2 cycles, each cycle consisting of 2 meetings and 4 stages, namely planning, action, observation and reflection. The subjects of this study were class VIIII students totaling 32 people. The instruments of data collection used in this study were observations supported by questionnaires and interviews.Based on the results of the research that has been done, it can be concluded that the results of observations of students 'creativity with the application of the Resource Based Learning approach in the first cycle of the 1st meeting of students' creativity are still low, that is, an average of 43.6%, then at the second meeting which is 64.2% of what is expected so that the researcher must continue the research to cycle II. In the second cycle the third meeting of students' creativity became 74.3% then at the 4th meeting which was 85.4%. While the results of the questionnaire in the first cycle with an average of 66% and in the second cycle to 80%. Based on observations supported by questionnaires and interviews, it can be concluded that the application of the Resource Based Learning approach succeeded in increasing students' creativity on the subject of circles in class VIIII SMP Negeri 8 Padangsidimpuan.